“Sexo, drogas y reggaetón”: lectura de HP (Hans Pozo), de Luis Barrales - Opazo, Cristián (Latin American Theatre Review, 2011)
In this essay I offer a reading of HP (Hans Pozo) (2007), by Luis Barrales (Chile, 1978). My purpose is to describe the main rhetorical strategies through which the text discussesthe place of the marginal boy in the politics of desire in post-dictatorship culture (beginning in 1990). This exercise is based on three questions: How does Barrales’ writing represents the marginal boy’s body? How does this representation rewrite texts of the Chilean literary canon? And, why does the marginal boy’s anatomy seduce playwrights and critics? (CO, Article in Spanish)